THE DETERMINATION OF GOOD CORPORATE GOVERNANCE ON PROFIT MANAGEMENT IN HEALTHCARE SECTOR COMPANIES IN INDONESIA DURING AND AFTER THE COVID-19 PANDEMIC: DETERMINASI GOOD CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA PADA PERUSAHAAN SEKTOR KESEHATAN DI INDONESIA SELAMA DAN SETELAH PANDEMI COVID-19 - Syahputra, Rendy Aziz; Ijma; Lestari, Ayu Indah (Jurnal Actual Organization Of Economic, 2023)
Company managers are responsible for managing the company owner's resources entrusted to them. But on the other hand, managers also have an interest in improving their welfare. So there is a possibility that company management does not always act in the best interests of investors. To avoid these differences in interests, a concept is needed, namely the concept of Corporate Governance which aims to make the company healthier. This research aims to explain and analyze the determination of Good Corporate Governance on Profit Management. The research subjects were 6 health sector companies listed on the Indonesia Stock Exchange (BEI) in the 2018-2022 period. The analytical tool used is multiple linear regression analysis with the help of the IBM SPSS 26 statistical program. The results of multiple linear regression analysis show that Managerial Ownership and Institutional Ownership have a positive and significant effect on Profit Management, while the Audit Committee has a negative and significant effect on Management. The Independent Board of Commissioners doesn't influence earnings management.